(untitled) (Research, Society and Development, 2020)
The objective of this study was to understand the perception of SAMU professionals about urgent and emergency care for people who are under the effect of psychoactive substances. The research was carried out with a qualitative approach, carried out at the SAMU headquarters in a medium-sized city in Rio Grande do Sul. The semi-structured interview technique was used for data collection, thematic analysis revealed the results, the results which were divided into three themes: urgent and emergency care for people who are under the influence of psychoactive substances; The fear of suffering violence; and The importance of continuing education for the approach of users of psychoactive substances. The prejudice and stigma on the part of health professionals and, also, the difficulties in these services, were points perceived by the participants as influencing this service. In addition, it was also possible to observe that some professionals believe that SAMU would not be the ideal service for psychiatric care.